1975
DOI: 10.1002/cpt1975182180
|View full text |Cite
|
Sign up to set email alerts
|

Methadone in man: Pharmacokinetic and excretion studies in acute and chronic treatment

Abstract: The biologic disposition of methadone in acute and during chronic administration was studied in 12 human volunteers. In the acute study a biexponential methadone plasma level decay was observed. The acute primary half-life (t1/2) of 14.3 hr in combination with the acute secondary t1/2 of 54.8 hr were longer than the single exponential chronic t1/2 of 22.2 hr determined in the same subjects. The urinary and fecal excretion of methadone and its mono-N-demethylated metabolite increased from 22.2% in the acute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
2
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(85 citation statements)
references
References 5 publications
6
76
2
1
Order By: Relevance
“…The variability in this ratio between individuals was less marked (0.72-1.83) and this agrees with results of a recent study carried out in 22 heroin-dependent subjects, where the l-methadone:dmethadone ratio ranged from 0.63 to 2.40 [15]. The sharp increase in EDDP plasma concentration from 7 to 24 ngW ml -1 occurring in the d,l-methadone group after changing to d,l-methadone confirms suggestions that d,lmethadone induces its own metabolism [15,24,25]. The non-significant decrease in the mean l-methadone:dmethadone plasma concentration ratio from 1.20 on day 15 to 1.15 on day 22 is in accord with Eap et al [15], who suggested a preferential metabolism of l-methadone compared to d-methadone when changing to d,l-methadone.…”
Section: Discussionsupporting
confidence: 80%
“…The variability in this ratio between individuals was less marked (0.72-1.83) and this agrees with results of a recent study carried out in 22 heroin-dependent subjects, where the l-methadone:dmethadone ratio ranged from 0.63 to 2.40 [15]. The sharp increase in EDDP plasma concentration from 7 to 24 ngW ml -1 occurring in the d,l-methadone group after changing to d,l-methadone confirms suggestions that d,lmethadone induces its own metabolism [15,24,25]. The non-significant decrease in the mean l-methadone:dmethadone plasma concentration ratio from 1.20 on day 15 to 1.15 on day 22 is in accord with Eap et al [15], who suggested a preferential metabolism of l-methadone compared to d-methadone when changing to d,l-methadone.…”
Section: Discussionsupporting
confidence: 80%
“…Further investigations should also be enzyme induction and other adaptive changes on the metabolism of methadone [25,28,36,49,50]. Whether aimed at clarifying the roles of plasma binding and enantioselective kinetics [48], and the influence of autothese complexities present formidable obstacles to the 4 From population analysis with t 1/2,z as a primary parameter with a log-normal distribution staff of the Leeds Addiction Unit for their assistance.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…as a result, its withdrawal or dose reduction result in serious withdrawal symptoms and craving leading to relapse. It also has relatively short half-life of 14.3 hrs [5]. since substances with shorter half-life have greater addictive potential [6], methadone works as a kind of substituted drug of addiction.…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usementioning
confidence: 99%